A new species of Nemipterus (Pisces: Nemipteridae) from the Western Indian Ocean - Russell, Barry C.; Gouws, Gavin (Zootaxa, 2020)
A new species of threadfin bream, Nemipterus elaine, from the Western Indian Ocean is described. The new species is known so far only from off the coast of southern Mozambique, and appears most closely related morphologically and genetically to N. randalli Russell, 1986, but differs in having shorter pectoral and pelvic fins, and the upper caudal lobe produced to form a short, bright yellow filament (a long red trailing filament present in N. randalli). A key to the species of Nemipterus in the Western Indian Ocean is provided.